Strategic maintenance-management in Nigerian industries - Eti, Mark C.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2006)
A developing society needs to adapt to change and foster creativity. In the pursuit of continual improvement (e.g., reducing fossil-fuel consumption and waste, better service performance, greater availability and improved reliability), implementing wise maintenance-schedules is essential for contemporary organisations. Several studies of a wide range of Nigerian industries indicate that indigenous low availability and low productivity are endemic. The resulting closure of some of these industries has triggered off a realisation of the strategic challenges in maintenance management. In addition, the increasingly-competitive business environment in Nigeria has raised the strategic importance of maintenance functions, especially in organisations with significant investments in physical assets. Five strategic aspects of maintenance management have been identified, namely: maintenance methodology; support processes; organisation and work structuring; comparable culture; and general management policy. Three factors that permeate these dimensions are wise leadership, excellent communications and an understanding of the human factors involved.
Keywords: Strategy; Maintenance